2019
DOI: 10.1530/jme-18-0152
|View full text |Cite
|
Sign up to set email alerts
|

Stress and glucocorticoid receptor regulation of mitochondrial gene expression

Abstract: Glucocorticoids have long been recognized for their role in regulating the availability of energetic resources, particularly during stress. Furthermore, bidirectional connections between glucocorticoids and the physiology and function of mitochondria have been discovered over the years. However, the precise mechanisms by which glucocorticoids act on mitochondria have only recently been explored. Glucocorticoids appear to regulate mitochondrial transcription via activation of glucocorticoid receptors (GRs) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 65 publications
(75 reference statements)
1
49
0
4
Order By: Relevance
“…Moreover, the GC-GRα complex interacts with other transcription factors, such as nuclear factor-κB (NF-κB) or activator protein-1 (AP-1) and alters their transcriptional activities. A recent review reported on the GC regulation of mitochondrial transcription, via activation of mtGRE [ 10 ]. The degree of cytosolic GRα saturation is a direct modulator of the intensity of (therapeutic) GC genomic effects [ 11 ].…”
Section: Pharmacological Principles Of Glucocorticoid Actionsmentioning
confidence: 99%
“…Moreover, the GC-GRα complex interacts with other transcription factors, such as nuclear factor-κB (NF-κB) or activator protein-1 (AP-1) and alters their transcriptional activities. A recent review reported on the GC regulation of mitochondrial transcription, via activation of mtGRE [ 10 ]. The degree of cytosolic GRα saturation is a direct modulator of the intensity of (therapeutic) GC genomic effects [ 11 ].…”
Section: Pharmacological Principles Of Glucocorticoid Actionsmentioning
confidence: 99%
“…"Persistent Inflammation, Immunosuppression, and Catabolism Syndrome" (PICS) has been postulated as the underlying pathophysiology of chronic critical illness (CCI) (18,47). About 50% of sepsis patients have a debilitating condition characterized by a self-perpetuating cycle of persistent low-grade systemic inflammation mimicking chronic stress (elevated cortisol) (44,48,49), glucocorticoid resistance, altered hemostasis (50,51), mitochondrial dysfunction (52,53), and accelerated inflamm-aging (9,54), with increased risk for chronic inflammatory systemic diseases (7,55). The evolutionary trade-off between acutely beneficial and chronically harmful homeostatic corrections was the subject of a recent review (7).…”
Section: Innate Immunity and Nuclear Factor-κbmentioning
confidence: 99%
“…After GC binding takes place in the cytoplasm, the activated GC-GRα complex can either (i) bind to several pro-inflammatory transcription factors, or (ii) act as a transcription factor, after translocation into the nucleus and mitochondria (69,82). Glucocorticoids regulation of mitochondrial transcription via activation of mtGRE was the subject of a recent review (53). In pathway (i), the activated GC-GRα complex interacts directly with activated transcription factors NF-κB and AP-1, leading to the transcriptional repression of major downstream proinflammatory factors.…”
Section: Glucocorticoid Receptor-alphamentioning
confidence: 99%
“…We observed the elevated GR level in the stressed rats only in SOL muscle. A possible mechanism could be linked with the fact that only GR (as opposed to MR) is found in mitochondria, suggesting that GRs drive the direct actions of glucocorticoids on mitochondria [34].…”
Section: Discussionmentioning
confidence: 99%